Leucocyte profile and offspring production of guinea pig (Cavia cobaya) given Anredera cordifolia leaf extract - Wijayanti, D.; Setiatin, E. T.; Kurnianto, E. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The objective of this study was to determine leucocyte and offspring production of guinea pig (Cavia cobaya) giving Anredera cordifolia leaf extract. Materials used were female 16 heads of guinea pig with body weight of 425g. The treatments were an extract of A. cordifolia leaf at doses of 0, 10, 50 and 90 mg/head, designated as T0, T1, T2 and T3, respectively. A. cordifolia leaf extract was administered orally from 10 days prepartum to 10 days postpartum. Blood was taken at 10 days prepartum and 10 days postpartum. Total birth of the offspring was observed. Data were analyzed by analysis of variance and if there was effect of treatment, then continued with Duncan multiple range test and Chi-Square test for fetal production between the given A. cordifolia leaf extract and control. The result showed that there was no significant difference for 10 days prepartum after addition of A cordifolia leaf extract treatment. The postpartum treated showed a total 50 mg/head level increaed for monocytes than that of level 0, 10 and 90 mg/head. Ten days postpartum treatment showed the total increase for leucocyte and monocytes total were 50 and 90 mg/head, respectively compared to 10 mg/head level. Total lymphocyte of 90 mg/head increased compared to level 10 and 50 mg/head. The highest total neutrophil as found at level of 50 mg/head which increased compared to the level of 0 and 10 mg/head. ProvisioningA. cordifolialeaf extract at doses level of 50 and 90 mg/head could increase litter size (P<0.05; χ2=9.267) and decreased offspring mortality (P<0.05; χ2=6.4). In conclusion, by giving 50 mg/head A. cordifolia leaf extract could increase leucocyte profile and offspring production of guinea pig.